PENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK KELAS XI IPA SMA NEGERI 3 PADANG - Annisa Tria Rahmadhani (Departemen Matematika, 2020)
Mathematical concept understanding must be owned by students as the basic ability of learning mathematics. But, the truth showed that students’ mathematical concept understanding of eleventh graders SMA Negeri 3 Padang were low. Based on observation result, the application of learning in school tended to be teacher center, so they were not involved actively in learning activity. Then, it needed a model that can actively involve students in learning activity. The solution was implementing Discovery Learning model as a model to train them constructing their own mathematical concept understanding. The goal of this research was to compare the difference between mathematical concept of students who learned by using discovery learning model and who learned conventional learning. The type of research was quasy experiment with Randomized Control-Group Only Design and use test of mathematical concept understanding as a instrument. Based on hypothesis result that mathematical concept understanding of students who learn by using discovery learning model is better than who learn by using conventional learning. Therefore, it can be concluded that discovery learning model affects on mathematical concept understanding. Keywords — Discovery Learning Model, Mathematical Concept Understanding